2015
DOI: 10.1210/me.2014-1275
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and ER Stress Regulate Branched-Chain Amino Acid Uptake and Metabolism in Adipocytes

Abstract: Inflammation plays a critical role in the pathology of obesity-linked insulin resistance and is mechanistically linked to the effects of macrophage-derived cytokines on adipocyte energy metabolism, particularly that of the mitochondrial branched-chain amino acid (BCAA) and tricarboxylic acid (TCA) pathways. To address the role of inflammation on energy metabolism in adipocytes, we used high fat-fed C57BL/6J mice and lean controls and measured the down-regulation of genes linked to BCAA and TCA cycle metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 37 publications
2
34
1
1
Order By: Relevance
“…However, the phosphorylation of the BCKDH complex was increased only in SCAT, suggesting a reduced oxidative capacity. In contrast to what has been described in rodents [23], the present results suggest for the first time the existence of a SCAT-specific regulation. This discordance with other species might be explained by the fact that in humans, increased VAT deposition is associated with an increased risk for IR and although SCAT is associated with improved or preserved insulin sensitivity, and mitigated risk for developing type 2 diabetes and other metabolic derangements [24].…”
Section: Fasting Metabolism Of Bcaa and Relation To The Ir Phenotypecontrasting
confidence: 99%
“…However, the phosphorylation of the BCKDH complex was increased only in SCAT, suggesting a reduced oxidative capacity. In contrast to what has been described in rodents [23], the present results suggest for the first time the existence of a SCAT-specific regulation. This discordance with other species might be explained by the fact that in humans, increased VAT deposition is associated with an increased risk for IR and although SCAT is associated with improved or preserved insulin sensitivity, and mitigated risk for developing type 2 diabetes and other metabolic derangements [24].…”
Section: Fasting Metabolism Of Bcaa and Relation To The Ir Phenotypecontrasting
confidence: 99%
“…In line with this, we have reported increased expression of genes that are associated with mitochondrial branched-chain amino acid (BCAA) cycle such as Bckdha and Bcat2 , and citric acid or tricarboxylic acid (TCA) cycle such as Cs and Pdha1 with concomitant increase in leucine and pyruvate oxidation in Cpt1b m−/− muscle23. Previous studies have indicated that higher levels of TNFα are associated with decreased expression of BCAA/TCA cycle genes70. The lower levels of TNFα expression reported in our study are therefore consistent with the observed enhanced expression of BCAA and TCA cycle genes in Cpt1b m−/− mice.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, supplementing high fat diet with BCAAs induced insulin resistance despite reduced food intake and weight gain, and was associated with increased activity of JNK in muscle (Newgard et al, 2009). Interestingly, a recent report showed that exposure to inflammatory cytokines blocked the uptake and metabolism of BCAAs in adipocytes, which could underlie the elevated levels observed in obese patients (Burrill et al, 2015). In addition, exposure to the macromolecules synthesized by pathogenic and commensal species can also have marked immunomodulatory and metabolic consequences.…”
Section: Effects Of Nutrients and Metabolites On Inflammationmentioning
confidence: 99%